2023
DOI: 10.1080/2162402x.2023.2240670
|View full text |Cite
|
Sign up to set email alerts
|

In vitro vascular differentiation system efficiently produces natural killer cells for cancer immunotherapies

Yekaterina Galat,
Yuchen Du,
Mariana Perepitchka
et al.

Abstract: Background Immunotherapeutic innovation is crucial for limited operability tumors. CAR T-cell therapy displayed reduced efficiency against glioblastoma (GBM), likely due to mutations underlying disease progression. Natural Killer cells (NKs) detect cancer cells despite said mutations – demonstrating increased tumor elimination potential. We developed an NK differentiation system using human pluripotent stem cells (hPSCs). Via this system, genetic modifications targeting cancer treatment challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Therefore, utilizing 3D GSC neurospheres could better emulate the in vivo environment. Galat et al recently employed GSC neurospheres to assess NK cell function [25], though ensuring uniform sphere sizes at the outset, especially for high-throughput screening, is crucial yet challenging for enhancing assay accuracy. In addition, the influence of other immune cell players, such as T cells or macrophages, on the effects exerted by NK cells against GSCs in GBM microenvironment remains a pertinent question.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, utilizing 3D GSC neurospheres could better emulate the in vivo environment. Galat et al recently employed GSC neurospheres to assess NK cell function [25], though ensuring uniform sphere sizes at the outset, especially for high-throughput screening, is crucial yet challenging for enhancing assay accuracy. In addition, the influence of other immune cell players, such as T cells or macrophages, on the effects exerted by NK cells against GSCs in GBM microenvironment remains a pertinent question.…”
Section: Resultsmentioning
confidence: 99%
“…There has also been interest in natural killer (NK) cells for cell transfers other than CAR-T cells. NK cells have increased anti-tumour activity compared to T cells in glioblastoma due to T cell targeting mutations in the tumour ( Lieberman et al, 2019 ; Galat et al, 2023 ). Galat et al, 2023 differentiated human pluripotent stem cells into NK cells and assessed their cytotoxicity in vitro using DIPG cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…NK cells have increased anti-tumour activity compared to T cells in glioblastoma due to T cell targeting mutations in the tumour ( Lieberman et al, 2019 ; Galat et al, 2023 ). Galat et al, 2023 differentiated human pluripotent stem cells into NK cells and assessed their cytotoxicity in vitro using DIPG cell lines. They found that the cells could successfully engraft in peripheral blood samples and are cytotoxic against DIPG cells.…”
Section: Introductionmentioning
confidence: 99%